Pooled prevalence and subgroup variations of Tetralogy of Fallot among children and adolescents with congenital heart defect in Sub-Saharan Africa: A systematic review and meta-analysis - Geleta, Biniam Endale; Mulu, Abay (PloS one, 2025)
Tetralogy of Fallot is one of the critical congenital heart defects needing intervention within the first year of life. This review aims to systematically assess the prevalence of Tetralogy of Fallot among children and adolescents with congenital heart defects in Sub-Saharan Africa from January 2000 to January 2024. All original observational studies focused on children and adolescent population diagnosed with congenital heart defects within Sub-Saharan Africa; reported the primary outcome of interest were included. Prisma guidelines were utilized to perform this systematic review and meta-analysis. Electronic databases including Medline (PubMed), Scopus, Google Scholar, and African Index Medicus were searched. A weighted inverse variance random-effects model was employed to estimate the pooled prevalence of Tetralogy of Fallot. Thirty-one studies included encompassing a total of 11,265 participants from 15 Sub-Saharan African countries with representation from Southern (4 studies, 619 participants), Central (5 studies, 2,220 participants), Eastern (11 studies, 3,384 participants), and Western (11 studies, 5,042 participants). Cross-sectional studies comprised (25 studies, 8,909 participants), and cohort design (6 studies, 2,356 participants). The analysis revealed a pooled prevalence of 10% (95% CI: 9%; 12%) with I2 (77%, p-value < 0.01). The subgroup analysis based on geographic regions revealed statistically significant difference. The prevalence of Tetralogy of Fallot observed was found considerably higher compared to global estimate and reports of developed countries. In a subgroup analysis based on the geographic region, a surprisingly high prevalence was reported across all regions of Sub-Saharan Africa. The substantial disparities and high prevalence observed underscores the complex interplay of factors influencing occurrence of Tetralogy of Fallot. Identifying the true scope of Tetralogy of Fallot burden may help policymakers and healthcare providers to prioritize interventions, optimize resource allocation, and potentially improve its outcomes in Sub-Saharan Africa.